Persepsi Masyarakat terhadap Kualitas Layanan Bank Syariah: Studi Kasus di Kota Bandung - Nugraha, Adhi; Hendi Fauzi; Sofi Abdurazzaq (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Islamic banks have become an important part of the financial system in Indonesia, offering services based on sharia principles. However, public perception of the quality of Islamic bank services at the local level, such as in Bandung City, is still a topic that requires further research. This study aims to measure people's perceptions of the quality of Islamic bank services in Bandung City using quantitative research methods. Data was collected through a survey using questionnaires distributed to 300 respondents. Analysis was conducted using descriptive statistical methods and multiple linear regression to evaluate the relationship between service quality dimensions (tangible, reliability, responsiveness, assurance, and empathy) and customer satisfaction. The results showed that assurance and empathy dimensions have the most significant influence on public perception. This study provides practical recommendations for Islamic banks to improve their service quality.